Detection of adherence of Enterococcus faecalis in infected dentin of extracted human teeth using confocal laser scanning microscope: An In vitro Study - V Siddharth Nair; Moksha Nayak; M K Ramya; G Sivadas; C Ganesh; S Lakshmi Devi; Vaishnavi Vedam (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of this study is to detect in vitro adherence of Enterococcus faecalis to the infected dentinal tubules of human extracted teeth using confocal laser scanning microscope. Subjects and Methods: Roots from human premolar teeth (n = 40) were infected with E. faecalis strain the American Type Culture Collection 29212 in brain heart infusion for 21 days. After the experimental period, specimens were divided into two groups, Group A (n = 20), Group B (n = 20), and Group A specimens were stained with fluorescein diacetate dye for the detection of viability and adherence Group B were stained with acridine orange dye for detection of metabolic activity and adherence. Samples were washed, thoroughly sectioned and examined by confocal laser scanning microscopy. Computer-assisted determinants of fluorescence, bacterial viability, metabolic activity, and adherence were compared statistically. Results: E. faecalis was able to invade the dentinal tubules to a depth of 1-400 μm and adhere to 1-200 μm depth. Adherence (90%) was significantly higher in 1-100 μm using fluorescein diacetate and acridine orange dye. Conclusion: Adherence of E. faecalis as evaluated by confocal laser scanning microscope was highest at the depth of 1-100 μm which may have an impact on the shaping and cleaning procedures on the root canal.